ISOLASI Amylomyces rouxii DARI RAGI DAN TAPE SINKONG SERTA PRODUKSI ENZIM GLUKOAMILASE - , HAFIDZ NUR FACHRUR ROZI, Dr. Ir. Retno Indrati , M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Glucoamylase is one of starch degrading enzyme that can be used in food and non-food industry. Glucoamylase can be produced by mold, such as Amylomyces rouxii. A. rouxii has natural habitat on fermentated tape and can be isolated directly from tape starters or casava tape. The objetives of this research is to obtain A. rouxii isolate from tape starters and cassava tape found in Yogyakarta that produced high glucomyamylase activity. This study was also carried out to evaluate conditions for glucoamylase production from the A. rouxii. Isolation step was done using 2 kinds of tape starter and cassava tape from local market of Yogyakarta. The samples were inoculated in potato dextrose agar medium by the spread plate method. Screening of amylolitik activity from the isolates suspect were done by measuring iodine clear zone that surrounding the isolates. Microscopic morphology of the isolates were also observe. Production of glucoamylase were carried out in various medium containg basal salts and sekam, bekatul, or kethak as a carbon source. The enzyme activity was measured using soluble starch as a substrate and the reducing sugar was monitored by the method of cuppromonium complex. The results show that 6 strains of fungi were isolated from the samples. From these, three isolates showed the similar morphology with Amylomyces rouxii. A.rouxii B had highest glucoamylase activity. The best growth conditions of A.rouxii for producing glucoamylase enzyme were using sekam medium, and incubation at 37Â°C for 3 days. At these condition, the enzyme produced was 104.45 U/ gram medium.